Heart rate variability – how to interpret and follow general rules - Kwaśniewska, Anna; Niezgoda, Magdalena; Kondracka, Adrianna; Wójtowicz-Marzec, Monika; Gąsior, Jakub (Prenatal Cardiology, 2024)
Heart rate variability (HRV) is a parameter reflecting the autonomic modulation of the cardiovascular system, and its analysis is a non-invasive measure of autonomic nervous system (ANS) modulation of the heart. A high variability of HRV is interpreted as normal, while a reduced HRV indicates ANS imbalances and poor prognosis for patients. Scientific studies have confirmed that HRV is a prognostic factor for selected clinical conditions. Changes in the components of the HRV parameter may precede the onset of clinical symptoms. Interpretation of HRV is based on the evaluation of the electrocardiographic record. HRV analysis, based on a series of RR intervals, makes it possible to assess the risk of cardiac events and forecast the progression of the patient’s clinical condition. Changes in HRV, in addition to physiological causes, may also reflect mental or physical health problems. Many studies have shown that HRV during pregnancy can indicate blood pressure abnormalities or preeclampsia. Pregnant women with gestational hypertension have a higher ratio of low-frequency (LF) power to high-frequency (HF) power in early pregnancy compared to women with uncomplicated pregnancies. In addition, by examining the impact of depression and anxiety on HRV parameters, it has been shown that it may reflect the mental health of a pregnant woman. HRV parameters can illustrate the level of stress experienced by a pregnant woman.